Early breast cancer and axillary lymphadenectomy: is everything obvious? - Piekarski, Janusz; Nejc, Dariusz; Sęk, Piotr; Wroński, Konrad; Jeziorski, Arkadiusz (Contemporary Oncology/Współczesna Onkologia, 2004)
Patients with in situ breast cancers or small invasive breast cancer (T1a/b according to TNM classification) have good prognosis. However, the standards of surgical treatment of these patients are different. In patients with in situ cancers, axillary lymphadenectomy is not performed. In patients with T1a/b invasive cancers, axillary lymphadenectomy is part of standard surgical treatment. In situ breast cancers do not spread to lymph nodes and/or distant organs. Nevertheless, literature data indicate that in patients with in situ cancers, metastases in axillary lymph nodes are found in 1% of cases; micrometastases are found in up to 13% of cases. The undiagnosed foci of microinvasion are responsible for these metastases. In patients with T1a and T1b cancers, metastases in axillary lymph nodes are found in less than 20% of patients. It seems that in some patients with in situ breast cancer, axillary lymphadenectomy is reasonable. On the other hand, in the vast majority of patients with T1a/b cancer, axillary lymphadenectomy is an overtreatment. It is possible, using sentinel node biopsy, to indicate patients who should undergo the lymphadenectomy. Therefore, sentinel node biopsy should be considered in patients with in situ cancer as well as in patients with T1a/b invasive cancer.